CCAFS Gender Impact Pathway for South Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Gender Impact Pathway for South Asia. Prepared by CCAFS South Asia representatives during the Gender Training and Strategizing Workshop in Nairobi, Kenya in 2013. Documents the pathway for equality and impact in the region: identifies current gaps, measures to fill those gaps, and the targeted outcomes for these activities.